2019
DOI: 10.48175/ijarsct-6208
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Mechanical Properties of High Strength Concrete

Abstract: High strength concrete is widely used for construction of high rise structures like bridges and dams so on. But using high strength concrete cost us more. Alternatively we can use some admixtures which can increase strength indirectly. In this project we have used GGBS, MICROSILICA AND ALCCOFINE and CRYSO is 1% in chemical admixture. On conducting different trail mixes we have come to know that by using 0%, 5%,10%,15%,20% and 25% is tested in normal water for 3, 7, 28 days. The results showed the suitability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…A small peak located at 513 cm −1 is assigned to the torsional oscillations of some NH 3 + groups. 35 Moreover, after incubation of the Ser/P-g-C 3 N 4 /ITO electrode (Fig. 2(c), violet) with anti-SAA solution (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…A small peak located at 513 cm −1 is assigned to the torsional oscillations of some NH 3 + groups. 35 Moreover, after incubation of the Ser/P-g-C 3 N 4 /ITO electrode (Fig. 2(c), violet) with anti-SAA solution (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…The literature review found few researches on utilizing bamboo fiber as road construction material. Bamboo fibers reportedly increase concrete beam flexural strength and elasticity modulus [61]. Using bamboo fiber increased the stability of SMA mixtures compared to cellulose fiber or no fiber [62].…”
Section: Bamboo Fibermentioning
confidence: 94%